2023
DOI: 10.3390/membranes13010063
|View full text |Cite
|
Sign up to set email alerts
|

The Infarct-Reducing Effect of the δ2 Opioid Receptor Agonist Deltorphin II: The Molecular Mechanism

Abstract: The search for novel drugs for the treatment of acute myocardial infarction and reperfusion injury of the heart is an urgent aim of modern pharmacology. Opioid peptides could be such potential drugs in this area. However, the molecular mechanism of the infarct-limiting effect of opioids in reperfusion remains unexplored. The objective of this research was to study the signaling mechanisms of the cardioprotective effect of deltorphin II in reperfusion. Rats were subjected to coronary artery occlusion (45 min) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
(43 reference statements)
0
11
0
1
Order By: Relevance
“…These data indicate that AMPK, Jak-2, PKA, and NOS are not involved in the deltorphininduced cardiac tolerance to reperfusion injury (Figure 1). The PKA inhibitor H-89 did not affect the deltorphin II-induced increase in the cardiac tolerance to reperfusion [38]. Therefore, the signaling mechanism of the cardioprotective effect of deltorphin II differs from that of morphine.…”
Section: The Role Of Protein Kinases and No Synthase In The Infarct-l...mentioning
confidence: 83%
See 3 more Smart Citations
“…These data indicate that AMPK, Jak-2, PKA, and NOS are not involved in the deltorphininduced cardiac tolerance to reperfusion injury (Figure 1). The PKA inhibitor H-89 did not affect the deltorphin II-induced increase in the cardiac tolerance to reperfusion [38]. Therefore, the signaling mechanism of the cardioprotective effect of deltorphin II differs from that of morphine.…”
Section: The Role Of Protein Kinases and No Synthase In The Infarct-l...mentioning
confidence: 83%
“…Therefore, the signaling mechanism of the cardioprotective effect of deltorphin II differs from that of morphine. Wortmannin, a PI3K inhibitor, and PD98059, an inhibitor of the signal cascade consisting of MEK1/2 and ERK1/2, abolished the infarct-sparing effect of the peptide δ 2 -OR agonist [38]. It should be noted that all of the indicated inhibitors did not affect the infarct size in the reperfusion of the heart.…”
Section: The Role Of Protein Kinases and No Synthase In The Infarct-l...mentioning
confidence: 93%
See 2 more Smart Citations
“…We found that blocking peripheral opioid receptors completely abolished the infarct-reducing effect of RPost induced by hind limb I/R in rats [ 20 ]. It was detected that opioid peptide deltorphin II can mimic RPost [ 30 , 31 ].…”
Section: Experimental Datamentioning
confidence: 99%